A RESEARCH ON THE ESTABLISHMENT OF TOTAL QUALITY MANAGEMENT IN MUNICIPALITIES - Onur Kemal Yılmaz (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Municipalities are the most authorized local government administrations in almost every country. Therefore, they have a responsibility to serve the citizens at the highest level. Total Quality Management is one of the approaches that will help this. The aim of this study is to present concretely what needs to be done to establish Total Quality Management in municipalities. For this, the Analytic Hierarchy Process method was used. According to this method, alternatives are given to experts and they are asked to rank them to achieve the goal. As a result, the ranking was made by the experts who participated in the research as follows; training of municipal top executives, public demand, establishment of Total Quality Management Directorate in municipalities, development of municipal legislation, supervision of municipalities by the General Directorate of local administrations.